2022
DOI: 10.1093/cercor/bhac179
|View full text |Cite
|
Sign up to set email alerts
|

Attentional modulation of beta-power aligns with the timing of behaviorally relevant rhythmic sounds

Abstract: It is largely unknown how attention adapts to the timing of acoustic stimuli. To address this, we investigated how hemispheric lateralization of alpha (7–13 Hz) and beta (14–24 Hz) oscillations, reflecting voluntary allocation of auditory spatial attention, is influenced by tempo and predictability of sounds. We recorded electroencephalography while healthy adults listened to rhythmic sound streams with different tempos that were presented dichotically to separate ears, thus permitting manipulation of spatial–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 75 publications
(119 reference statements)
2
3
0
Order By: Relevance
“…Overall, the results are in line with studies indicating that temporal sensory predictions are implemented via beta oscillations (Foldal et al, 2023; Fujioka et al, 2015; Iversen et al, 2009; Morillon and Baillet, 2017; Rimmele et al, 2018; Saleh et al, 2010). Relatedly, Arnal et al (2015) reported that pre-target beta power was enhanced for correctly detected targets in a timing judgment task, along with a significantly enhanced cross-frequency coupling between pre-target delta phase and beta power.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Overall, the results are in line with studies indicating that temporal sensory predictions are implemented via beta oscillations (Foldal et al, 2023; Fujioka et al, 2015; Iversen et al, 2009; Morillon and Baillet, 2017; Rimmele et al, 2018; Saleh et al, 2010). Relatedly, Arnal et al (2015) reported that pre-target beta power was enhanced for correctly detected targets in a timing judgment task, along with a significantly enhanced cross-frequency coupling between pre-target delta phase and beta power.…”
Section: Discussionsupporting
confidence: 90%
“…At the neural level, the results replicated previous findings that modulations in beta-band power synchronize with a regular beat (Fujioka et al, 2015;Merchant et al, 2015) and encode temporal predictions (Foldal et al, 2023;Morillon and Baillet, 2017). Importantly, this study revealed that beta power is modulated in a top-down manner by the cue, enabling the neural system to flexibly adapt to different acoustic envelope shapes in accordance with task-specific demands, thereby enhancing sensory selection and performance.…”
Section: Beta-band Power Encodes Predictions About the Acoustic Envel...supporting
confidence: 86%
See 2 more Smart Citations
“…Recent research investigating motor-auditory connectivity during the grouping of musical beats into a march or waltz has highlighted the involvement of the motor system in active meter imagination, extending motor hypotheses from beat perception to hierarchical timing [31]. In summary, both the movement intention and rhythmic temporal prediction rely on overlapping neural structures/circuits, and exhibit specific power changes in the beta band [32].…”
Section: Introductionmentioning
confidence: 99%